Spatial Analysis of the Suitability of Residential Area Development to the Regional Spatial Plan of Ambon City, Indonesia, Based on the Slope Factor - Rakuasa, Heinrich; Viktor Vladimirovich Budnikov; Daniel Anthoni Sihasale (PT. Banjarese Pacific Indonesia, 2024)
This study examines the suitability of land for the development of residential areas in Ambon City, based on the slope factor. The methods used include spatial analysis by utilizing Digital Elevation Model (DEM) data and the Ambon City Regional Spatial Plan (RTRW), as well as satellite image interpretation to identify suitable and unsuitable areas for residential development. The results show that more than 56% of the total planned land area is in the highly suitable category, while areas with steep slopes have a high potential for landslide risk. The discussion emphasizes the importance of settlement development focusing on safe and suitable areas, and the need for strict regulations to protect communities from disaster risks. The findings provide a strong basis for policy makers to formulate spatial planning strategies that are sustainable and responsive to the geographical conditions of Ambon City.